TEACHING OF COMPUTER AIDED DESIGN SYSTEMS - Dabolins, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The objective of this paper is to analyze and describe computer-aided design training and its aspects. A traditional and technology-supported learning process is described with the purpose of analyzing computer-aided design training and provision of knowledge assessment, and identifying problems in the CAD system training. The article analyzes the learning process by defining its objectives, the necessity of student characterization, motivation analysis, the necessity of feedback and other basic components; it analyzes the training methods, provides insight into technology-supported learning process, identifies the provision and types of computer-aided design training and knowledge assessment as well as describes feedback and its role in the training process.Elaboration of an intellectual learning system would solve the problems associated with lack of feedback, lack of adaptivity and the emergence of plagiarism (since only the end result of the design is subjected to the test and not the whole process of creating it, it is easy to pass another’s work for one’s own). A solution to these problems would facilitate the work of the teacher and improve student learning outcomes.